Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/cdoe.12372
|View full text |Cite
|
Sign up to set email alerts
|

Foetal, neonatal and child vitamin D status and enamel hypomineralization

Abstract: 25(OH)D concentrations in prenatal, early postnatal and later postnatal life are not associated with the presence of HPSMs or with MIH at the age of six. Future observational research is required to replicate our findings. Furthermore, it is encouraged to focus on identifying other modifiable risk factors, because prevention of hypomineralization is possible only if the causes are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 34 publications
2
51
0
4
Order By: Relevance
“…21 Previous studies on the role of vitamin D intake suggest it could prevent progression of dental caries and periodontal diseases. 4,22,23 In this study all NS patients were using calcium and vitamin D in while receiving corticosteroids. Although NS patients had poor oral hygiene, they showed lower dmft/DMFT values compared with the control group, which might be related to the usage of Vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Previous studies on the role of vitamin D intake suggest it could prevent progression of dental caries and periodontal diseases. 4,22,23 In this study all NS patients were using calcium and vitamin D in while receiving corticosteroids. Although NS patients had poor oral hygiene, they showed lower dmft/DMFT values compared with the control group, which might be related to the usage of Vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of calcium and phosphorus help to improve healthy bone and teeth development. 4 In children with nephrotic syndrome, loss of 25-hydroxycholecalciferol (25-OH D) and vitamin D binding protein (VDBP) in the urine, alterations in calcium and phosphorus balance due to CS treatment, and inflammation in the pathogenesis lead to metabolic bone disease. 5 The storage in the bone mass that starts in fetal life and continues throughout childhood becomes stabilized in adulthood.…”
mentioning
confidence: 99%
“…Despite caries, the occurrence of enamel hypoplasia seems to be associated with low blood levels of vitamin D during pregnancy [62], whereas the occurrence of MIH seems not affected by fetal, postnatal and early childhood levels of vitamin D [59]. One study found no association between the occurrence of enamel defects and vitamin D in 1-and 2-year-old children born preterm [72].…”
Section: Hard Dental Pathological Processesmentioning
confidence: 99%
“…One study found that increased levels of vitamin Dcorrelated with a decreased incidence of MIH, 17 while another looking at foetal, neonatal and childhood vitamin D levels, found no correlation with MIH. 18 Caries A study looking at low maternal serum vitamin D levels during pregnancy found a significant association (P = 0.05) to early childhood caries among infants up to 1 years old. 19 Low vitamin D levels have also been shown to be associated with high caries risk, and the severity of decay in primary/mixed dentitions, 20,21,22 though the evidence for the permanent dentition is limited and further investigation is required.…”
Section: Enamel Defectsmentioning
confidence: 99%